Anti-reflection temperature-control photovoltaic panel coating and preparation method thereof

By using a coating composed of block copolymers and double-shell hollow nanoparticles on the photovoltaic panel, the problem of reducing power generation efficiency caused by the increase in the photovoltaic panel is solved, and the effect of improving power generation efficiency and extending life is achieved.

CN119242124AActive Publication Date: 2025-01-03TITANIUM TECHNOLOGY (HANGZHOU) CO LTD

Patent Information

Application Number
CN202411543614.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-03
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The temperature of the photovoltaic panel increases in the process of increasing the light transmittance, resulting in a decrease in power generation efficiency, and aging of long-term high temperatures, shortening service life, and increasing maintenance and replacement costs.

Method used

The temperature-enhancing photovoltaic panel coating consisting of block copolymer, double-shell hollow nanoparticles and aminopropyl trimethoxysilane is used to reduce the reflectance through a unique double-layer nano hollow structure, improve the heat dissipation performance, and form homogeneous Films to improve transmittance and power generation efficiency.

Benefits of technology

It significantly improves the power generation efficiency of photovoltaic panels, keeps the temperature within the appropriate range, extends service life, reduces maintenance costs, and enhances surface self-cleaning performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242124A_ABST
    Figure CN119242124A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-reflection temperature-control photovoltaic panel coating and a preparation method thereof. The anti-reflection temperature-control photovoltaic panel coating is prepared from the following components: 146 to 156 parts of segmented copolymer, 230 to 245 parts of double-layer shell hollow nano particles and 15 to 17 parts of aminopropyl trimethoxy silane, the block copolymer is a triblock copolymer of 48-52 parts of thiolactone acrylamide, 90-94 parts of perfluorooctyl ethyl acrylate and 8-10 parts of methyl methacrylate, the inner layer of the double-layer shell hollow nanoparticle is indium tin oxide, and the outer layer of the double-layer shell hollow nanoparticle is silicon dioxide. The coating provided by the invention can improve the light transmittance, also significantly enhances the heat dissipation performance of the photovoltaic panel, and significantly improves the power generation efficiency of the photovoltaic panel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and specifically relates to a photovoltaic panel coating with enhanced transmittance and temperature control and a preparation method thereof. Background Art

[0002] Photovoltaic power generation, as a new type of clean energy, has many advantages over traditional power generation, such as environmental protection, pollution-free, and noise-free. It is a sustainable new energy that my country has vigorously developed in recent years. By the end of 2023, the installed capacity of solar power generation will be about 610 million kilowatts, a year-on-year increase of 55.2%; the installed capacity of wind power will be about 440 million kilowatts, a year-on-year increase of 20.7%, demonstrating the strong growth momentum and development prospects of the photovoltaic industry. However, with the rapid development of the photovoltaic industry, the problem of power generation efficiency of photovoltaic systems has become increasingly prominent. At present, research on improving the light energy conversion rate focuses on improving the transmittance of photovoltaic panels, but this also causes the temperature of photovoltaic panels to rise, which will reduce the power generation rate. Studies have shown that for every 10°C increase in the temperature of photovoltaic panels, the power generation efficiency will decrease by about 1%. Especially in the high temperature period in summer, the power generation efficiency of high-transmittance photovoltaic panels may decrease by more than 20%. In addition, long-term high temperature will accelerate the aging of photovoltaic panels, shorten their service life, and increase the cost and frequency of maintenance and replacement. Therefore, research on reducing the temperature of photovoltaic panels and improving the efficiency of photovoltaic power generation has become particularly urgent. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a photovoltaic panel coating with enhanced transmittance and temperature control and a preparation method thereof, which can improve the light transmittance while also significantly enhancing the heat dissipation performance of the photovoltaic panel, thereby significantly improving the power generation efficiency of the photovoltaic panel.

[0004] The technical solution adopted by the present invention is:

[0005] A photovoltaic panel coating with enhanced transmittance and temperature control is prepared by mixing and reacting raw materials including the following components: 146-156 parts of block copolymer, 230-245 parts of double-shell hollow nanoparticles, and 15-17 parts of aminopropyltrimethoxysilane; the block copolymer is a triblock copolymer of 48-52 parts of thiolactone acrylamide, 90-94 parts of 8-10 parts of perfluorooctylethyl acrylate and methyl methacrylate, and the double-shell hollow nanoparticles are double-shell hollow nanoparticles with an inner layer of indium tin oxide and an outer layer of silicon dioxide; the above component parts are all parts by weight, and the molecular formula of the thiolactone acrylamide is as follows:

[0006]

[0007] Perfluorooctyl ethyl acrylate will reduce the free energy of the coating surface and increase the hydrophobicity and oleophobicity. Methyl methacrylate can also assist the film-forming property of the coating. The increase in its addition amount will enable the coating to form a more homogeneous film after curing, thus improving the transmittance to a certain extent.

[0008] The method for preparing the above-mentioned anti-reflection temperature-control photovoltaic panel coating comprises the following steps:

[0009] (1) Dissolve 48-52 parts of thiolactone acrylamide, 90-94 parts of perfluorooctyl ethyl acrylate and 8-10 parts of methyl methacrylate in an appropriate amount of organic solvent, add an appropriate amount of crosslinking agent, and after the reaction is complete, obtain a block copolymer solution. The molecular formula of the thiolactone acrylamide is as follows:

[0010]

[0011] (2) dispersing 230-245 parts of double-shell hollow nanoparticles in a solution of a block copolymer, adding 15-17 parts of aminopropyltrimethoxysilane, stirring and slowly adding a catalyst, and obtaining a coating after the reaction is complete; the double-shell hollow nanoparticles are double-shell hollow nanoparticles with an inner layer of indium tin oxide and an outer layer of silicon dioxide; the above components are all in parts by weight.

[0012] Preferably, the cross-linking agent is any one of azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate, and the added amount is 1.7-2.5 wt%.

[0013] Preferably, the catalyst is dibutyltin dilaurate, and the added amount is 1.8-3.2 parts.

[0014] Preferably, the organic solvent in step (1) is butyl acetate, and the reaction temperature in step (2) is room temperature, which can be heated to above 30° C. to accelerate the reaction rate.

[0015] Further, the thiolactone acrylamide is prepared by the following steps:

[0016] S1. dispersing 14-16 parts of DL-homocysteine ​​thiolactone hydrochloride in an organic solvent;

[0017] S2, add 18-18.5 parts of acryloyl chloride and 24.5-25.5 parts of triethylamine dropwise to the solution obtained in S1, stir, and control the temperature at 0-5°C until the reaction is complete;

[0018] S3, washing with water to remove the byproduct salt generated by the reaction, and evaporating to remove the organic solvent;

[0019] S4, using an organic solvent as an eluent, purifying the product of S3 using a silica chromatography column to obtain thiolactone acrylamide;

[0020] The above component parts are all by weight.

[0021] Preferably, the organic solvent in step S1 is dichloromethane.

[0022] Preferably, the organic solvent in step S4 is a mixed solution of ethyl acetate and n-hexane in a volume ratio of 1:1.

[0023] Preferably, the evaporation operation in step S3 is performed by rotary evaporation under a condition of 5 mbar to remove the solvent.

[0024] Further, the double-shell hollow nanoparticles are prepared by the following steps:

[0025] B1. Dispersing 200-205 parts of negatively charged nano-polystyrene microspheres with a particle size of 40-60 nm and 75-85 parts of nano-indium tin oxide particles in a volatile organic solvent, wherein the particle size of the nano-indium tin oxide is less than half of the nano-polystyrene microspheres; allowing the indium tin oxide particles to be adsorbed on the surface of the nano-polystyrene microspheres through electrostatic force; the above operation can be performed by ultrasonic dispersion to improve the dispersion efficiency.

[0026] B2, dispersing 15.5-16.5 parts of hexadecyltrimethylammonium bromide in an organic solvent, adding appropriate amounts of water and ammonia water, and mixing to form a uniform solution; slowly adding 155-165 parts of tetraethyl silicate, mixing and reacting completely, and the amount of water added is sufficient to allow the tetraethyl silicate to react completely;

[0027] B3, after evaporating and removing the organic solvent, the reaction product is placed in a muffle furnace and calcined to remove the polystyrene microsphere template, thereby obtaining double-shell hollow nanoparticles with an inner layer of indium tin oxide and an outer layer of silicon dioxide;

[0028] Preferably, the organic solvents in steps B1 and B2 are both isopropanol, and the calcination temperature in step B3 is 550°C.

[0029] The anti-reflection and temperature-controlling photovoltaic panel coating provided by the present invention forms a coating by utilizing a unique double-layer nano hollow structure, which can reduce the reflectivity of the photovoltaic panel glass to a certain extent, reduce the reflection of incident sunlight, and increase the effective light energy intake of the photovoltaic cell assembly, thereby improving the power generation; at the same time, the coating has excellent heat dissipation effect, and can effectively solve the problem of excessive temperature of the photovoltaic cell assembly caused by long-term sunlight exposure, maintain it within a suitable operating temperature range, and ensure the stability of power generation efficiency; it has excellent surface self-cleaning performance, and can keep the surface of the photovoltaic panel clean for a long time, greatly reducing the cleaning cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1Comparison curve of transmittance of photovoltaic panel glass coated with the coating prepared in Example 1 of the present invention and untreated photovoltaic panel glass in the solar radiation spectrum region.

[0031] Figure 2 The emissivity of the photovoltaic panel coated with the coating prepared in Example 1 of the present invention in the infrared light region.

[0032] Figure 3 Temperature difference curve between a photovoltaic panel coated with the coating prepared in Example 1 of the present invention and an untreated photovoltaic cell under long-term sunlight.

[0033] Figure 4 Comparison curve of power generation efficiency of a photovoltaic panel coated with the coating prepared in Example 1 of the present invention and an untreated photovoltaic panel before and after long-term sunshine exposure. DETAILED DESCRIPTION

[0034] The specific implementation of the present invention is described in detail below in conjunction with specific implementation examples, but the present invention is not limited to the given examples.

[0035] The quick-drying transparent super-hydrophobic and oleophobic coating suitable for photovoltaic panels is prepared by raw materials including dipentaerythritol hexa(3-mercaptopropionic acid) ester, perfluorooctyl ethyl acrylate, glycidyl methacrylate, 2,2-dimethoxy-2-phenylacetophenone, lithium salt of bis(fluorosulfonyl)imide, triethylene glycol dimethyl ether, ethylenediamine, and fluorocarbon resin (FEVE).

[0036] Embodiment 1:

[0037] The specific preparation method of the anti-reflection temperature-control photovoltaic panel coating provided by the present invention is as follows:

[0038] (1) 15.36 g of DL-homocysteine ​​thiolactone hydrochloride was dispersed in 200 mL of dichloromethane and stirred continuously for more than 30 minutes in an ice-water bath at 0-5° C. to ensure complete dispersion; then 18.1 g of acryloyl chloride and 25.3 g of triethylamine were added dropwise to the above solution and stirred continuously for 24 hours in an ice-water bath at 0-5° C. until the reaction was complete; the solution was rinsed three times with deionized water to remove the byproduct salt generated by the reaction, and then the solvent was removed by rotary evaporation at 5 mbar; then the product was purified by silica chromatography using a mixed solution of ethyl acetate and n-hexane (volume ratio 1:1) as the eluent, and the final solid after purification was 50.6 g of the synthesized thiolactone acrylamide;

[0039] (2) dissolving the thiolactone acrylamide prepared in step (1), 91.09 g of perfluorooctyl ethyl acrylate and 8.8 g of methyl methacrylate in 200 mL of butyl acetate, adding 1.72 g of azobisisobutyronitrile, and stirring the mixture at 35° C. for 2 hours to obtain a block copolymer solution, wherein the amount of the block copolymer is 150 g;

[0040] (3) 201 g of negatively charged monodisperse nano polystyrene microspheres (PS microspheres) with a particle size of 50 nm and 80 g of indium tin oxide (ITO) nanoparticles with a particle size of 20 nm were added to 500 mL of isopropanol, ultrasonically dispersed in an ultrasonic water bath for 1 hour, and stirred for 30 minutes; then 16 g of hexadecyltrimethylammonium bromide was dissolved in the isopropanol, and 70 mL of deionized water and 5 mL of concentrated ammonia water were added thereto, and stirred at room temperature for 30 minutes; then 160 g of tetraethyl silicate was dropwise added to the above solution, and the mixture was stirred until the reaction was complete; after rotary evaporation to remove the isopropanol solvent, the solution was placed in a muffle furnace and calcined at 550° C. for 2 hours to remove the polystyrene microsphere template, and 237 g of double-shell hollow nanoparticles with an inner layer of indium tin oxide and an outer layer of SiO2 were prepared;

[0041] (4) The double-shell hollow nanoparticles prepared in step (3) are dispersed in the solution prepared in step (2), 15.75 g of aminopropyltrimethoxysilane is added, and an appropriate amount of butyl acetate can be added to avoid excessive viscosity. 2.6 g of catalyst dibutyltin dilaurate is added dropwise at 50° C. while stirring, and the reaction is continued for 1 hour to obtain a coating.

[0042] Example 2

[0043] The difference between this embodiment and embodiment 1 is that the amount of each component added is 16g of DL-homocysteine ​​thiolactone hydrochloride, 18.5g of acryloyl chloride, 94g of perfluorooctyl ethyl acrylate, 8g of methyl methacrylate, 2g of azobisisobutyronitrile, and 200g of nano polystyrene microspheres. The amount of the intermediate product thiolactone acrylamide is 52g, and the block copolymer is 156g. The rest is the same as in embodiment 1.

[0044] Example 3

[0045] The difference between this embodiment and embodiment 1 is that the addition amount of each component is 14g of DL-homocysteine ​​thiolactone hydrochloride, 18g of acryloyl chloride, 90g of perfluorooctyl ethyl acrylate, 10g of methyl methacrylate, 2.5g of azobisisobutyronitrile, and 200g of nano polystyrene microspheres. The amount of the intermediate product thiolactone acrylamide is 48g, and the block copolymer is 146g. The rest is the same as in embodiment 1.

[0046] Example 4

[0047] The difference between this embodiment and embodiment 1 is that the amount of indium tin oxide added is 75 g, and the amount of dibutyltin dilaurate is 1.8 g. The rest is the same as embodiment 1.

[0048] Example 5

[0049] The difference between this embodiment and embodiment 1 is that the amount of indium tin oxide added is 85 g, and the amount of dibutyltin dilaurate is 3.2 g. The other aspects are the same as those of embodiment 1.

[0050] Example 6

[0051] The difference between this embodiment and embodiment 1 is that the added amount of each component is 200g of nano polystyrene microspheres, 15.5g of hexadecyltrimethylammonium bromide, 155g of tetraethyl silicate, 15g of aminopropyltrimethoxysilane, and 230g of the intermediate product double-shell hollow nanoparticles. The rest is the same as embodiment 1.

[0052] Example 7

[0053] The difference between this embodiment and embodiment 1 is that the added amount of each component is 205g of nano polystyrene microspheres, 16.5g of hexadecyltrimethylammonium bromide, 165g of tetraethyl silicate, 17g of aminopropyltrimethoxysilane, and 245g of the intermediate product double-shell hollow nanoparticles. The rest is the same as embodiment 1.

[0054] After the glass substrate used for the photovoltaic panel was rinsed twice with anhydrous ethanol and deionized water alternately, the coating prepared in the above embodiment was sprayed onto the surface of the photovoltaic glass panel, and the glass panel was kept horizontal during the spraying process. After curing for 30 minutes at 80°C, a coating with an enhanced transmittance and temperature control was prepared on the surface of the photovoltaic glass panel. Then, the transmittance of the coating in the solar radiation spectrum region, the emissivity in the infrared light region, the hydrophobic and oleophobic properties, and the power generation efficiency were tested respectively.

[0055] The coating prepared in the embodiment of the present invention was tested for performance as follows:

[0056] Solar radiation spectral transmittance: The transmittance of the samples (coated-glass and original glass) to visible light was tested using an Agilent Cary 5000 UV-Vis-NIR spectrophotometer. The size of the test sample was 7.5 cm × 2.5 cm, and a glass slide of the same size was selected as a control sample during the test. The transmittance of air was set as the baseline for the test. The test wavelength range was 300 nm to 1800 nm.

[0057] Emissivity in the infrared region: The emissivity of the coated photovoltaic panels in the long-wave infrared region (6-25 microns) was tested using the Thermo Fisher Nicolet iS50.

[0058] Contact angle: The contact angle of water droplets / oil droplets (if not otherwise specified, the oils used in the test here are all gasoline, i.e., a mixture of aliphatic hydrocarbons and cycloalkanes) on the coating surface was measured using the KRüSSDSA25S optical contact angle analysis system. For the measurement of the contact angle in a non-moving state, a water droplet / oil droplet (~10 μL) was first added to the sample surface by a motor-controlled syringe. When the droplet is stable, a side image is taken with a camera, and the software is used for fitting calculation to obtain the static contact angle value of the water droplet / oil droplet on the coating surface.

[0059] Rolling / sliding angle: The sliding angle of water / oil droplets on the coating surface was measured using the KRüSSDSA25S optical contact angle analysis system. For the sliding angle measurement, a motor-controlled rotatable test platform is used to tilt the sample, and the rotation angle of the platform is displayed in real time on a computer connected to the motor. At the beginning of the test, the initial inclination angle of the platform is maintained at 0°. After a water / oil droplet (approximately 10 μL) is added to the coating surface via a syringe, the motor is controlled to rotate the platform. The rotation stops at the moment the droplet begins to roll on the surface, and the rotation angle displayed on the computer is recorded as the rolling angle. Each sample is measured at three different positions to reduce data errors.

[0060] Comparative test of power generation efficiency: The current density-voltage curve was tested by the PROVA 200A solar cell analyzer. The solar light source during the test was provided by the SOLARBEAM-06-3A sunlight simulator of Yiguang Technology, simulating AM 1.5 sunlight of about 100mW cm -2 The test samples were subjected to current density-voltage tests at the beginning of irradiation and after 2 hours of continuous irradiation to simulate the situation when the temperature of the photovoltaic panel rises.

[0061] The above test method was used to test the performance of the coatings formed by coating the photovoltaic glass panels with the coatings prepared in each embodiment. The results are shown in the following table:

[0062]

[0063] During the preparation process of the coating of the present invention, nano-ITO particles are adsorbed to the surface of negatively charged PS nano-microspheres in the solvent due to electrostatic interaction forces, forming ITO@PS nano-microspheres with a core-shell structure. Subsequently, hexadecyltrimethylammonium bromide is added as a catalyst in a mixed solvent of isopropanol, water and concentrated ammonia water, and TEOS is hydrolyzed on the surface of the ITO@PS nano-microspheres with the ITO@PS nano-microspheres as the core, and finally a three-layer structure of SiO2@ITO@PS nano-microspheres is formed. Finally, after high-temperature calcination to remove the core PS, a final double-shell hollow nano-microsphere with ITO as the inner shell and SiO2 as the outer shell is prepared. This double-shell hollow nano-microsphere structure can effectively enhance the transmittance of beneficial light, and at the same time has a good reflection effect on the infrared light with a wavelength greater than 1.1 microns.

[0064] Comparison curve of transmittance of coated photovoltaic panel glass and untreated photovoltaic panel glass in the solar radiation spectrum region ( Figure 1 ) It can be seen that the coating of the present invention has excellent anti-reflection and anti-transmission properties. In the visible light region and near-infrared I region (the part with a wavelength less than 1.1 microns), the pass rate reaches about 95%, which is about 4-5 percentage points higher than the untreated glass. This allows the photovoltaic panels coated with the coating to have more photon energy absorbed by the semiconductor material within the working light domain of the silicon-based semiconductor material, thereby improving the photoelectric conversion efficiency and increasing the power generation. Infrared light outside the working light domain does not contribute to power generation and will also be converted into excess heat, which will increase the temperature of the photovoltaic modules and affect the working efficiency of the photovoltaic modules, so it should be reflected as much as possible. From Figure 1 It can be seen that the transmittance of infrared light in the near-infrared II region (the part with a wavelength greater than 1.1 microns) is extremely low, which can greatly reduce the negative thermal effects of useless infrared light on photovoltaic modules.

[0065] Figure 2 The emissivity spectrum of the coated photovoltaic panel in the long-wave infrared region shows that there is an extremely high transmittance window at 8-13 microns in the long-wave infrared region, which allows infrared rays inside the atmosphere to pass through the atmosphere and be emitted into outer space. The coated photovoltaic panel has an extremely high emissivity in the atmospheric window area, which allows the heat of the photovoltaic module to be dissipated in the form of thermal radiation to outer space where the temperature is only 3K, achieving zero-energy heat dissipation of the photovoltaic module, keeping it in a suitable operating temperature window, reducing the temperature of the photovoltaic module, and maintaining a high power generation efficiency. In order to more intuitively demonstrate the temperature control effect of the anti-reflection and temperature-control photovoltaic panel coating on the photovoltaic panel, the surface temperature of the coated photovoltaic panel and the untreated photovoltaic panel was monitored in real time using thermocouples ( Figure 3), during the one-day monitoring, it can be seen that as time approaches noon, the intensity of solar radiation gradually increases, and the ambient atmospheric temperature also gradually increases. The surface temperature of the untreated photovoltaic panel reached nearly 55°C, while the surface temperature of the coated photovoltaic panel was only about 45°C, which was about 10°C lower. According to reports, for every 1°C increase in the temperature of the photovoltaic module, its working efficiency decreases by about 0.35%. In other words, during the test, the working performance of the coated photovoltaic panel is at least about 3.5% higher than that of the untreated photovoltaic panel.

[0066] like Figure 4 As shown in the figure, the changes in the power generation performance of the photovoltaic panel coated with the coating and the untreated photovoltaic panel before and after sunlight exposure for a certain period of time can be seen. After the coating of the coating of the present invention, the power generation efficiency (current density) of the photovoltaic panel is significantly increased. Due to the anti-reflection and anti-transmission properties of the coating, the initial power generation efficiency of the photovoltaic panel coated with the coating is higher than that of the untreated photovoltaic panel, which is manifested as a higher open circuit voltage and short circuit current.

[0067] Since the coated photovoltaic panels have a synergistic temperature control effect of reflecting near-infrared and high far-infrared emissions, the temperature of the coated photovoltaic panels is lower than that of untreated photovoltaic panels, reducing the negative impact of light irradiation heat generation on photovoltaic modules. Figure 4 It can be seen that after being irradiated by sunlight, the power generation efficiency of the photovoltaic panel coated with the coating of the present invention is much higher than that of the untreated photovoltaic panel, which fully demonstrates that the coating of the present invention has excellent light transmission and temperature control effects.

[0068] The present invention has been described in detail above in conjunction with specific embodiments. However, the present invention is not limited to the above description. Various changes made within the knowledge of those skilled in the art without departing from the concept of the present invention still fall within the protection scope of the present invention.

Claims

1. A photovoltaic panel coating with enhanced transmittance and temperature control, characterized in that: The invention is prepared by mixing and reacting raw materials including the following components: 146-156 parts of block copolymer, 230-245 parts of double-shell hollow nanoparticles, and 15-17 parts of aminopropyltrimethoxysilane; the block copolymer is a triblock copolymer of 48-52 parts of thiolactone acrylamide, 90-94 parts of 8-10 parts of perfluorooctylethyl acrylate and methyl methacrylate; the double-shell hollow nanoparticles are double-shell hollow nanoparticles with an inner layer of indium tin oxide and an outer layer of silicon dioxide; the above component parts are all parts by weight, and the molecular formula of the thiolactone acrylamide is as follows:

2. A method for preparing a photovoltaic panel coating with enhanced transmittance and temperature control, characterized in that: It includes the following steps: (1) Dissolve 48-52 parts of thiolactone acrylamide, 90-94 parts of perfluorooctyl ethyl acrylate and 8-10 parts of methyl methacrylate in an appropriate amount of organic solvent, add an appropriate amount of crosslinking agent, and after the reaction is complete, obtain a block copolymer solution. The molecular formula of the thiolactone acrylamide is as follows: (2) dispersing 230-245 parts of double-shell hollow nanoparticles in a solution of a block copolymer, adding 15-17 parts of aminopropyltrimethoxysilane, stirring and slowly adding a catalyst, and obtaining a coating after the reaction is complete; the double-shell hollow nanoparticles are double-shell hollow nanoparticles with an inner layer of indium tin oxide and an outer layer of silicon dioxide; the above components are all in parts by weight.

3. The method for preparing a photovoltaic panel coating with anti-reflection and temperature control according to claim 2, characterized in that: The cross-linking agent is any one of azobisisobutyronitrile, azobisisoheptanenitrile or dimethyl azobisisobutyrate, and the added amount is 1.7-2.5wt%.

4. The method for preparing a photovoltaic panel coating with anti-reflection and temperature control according to claim 2, characterized in that: The catalyst is dibutyltin dilaurate, and the added amount is 1.8 to 3.2 parts.

5. The method for preparing a photovoltaic panel coating with anti-reflection and temperature control according to claim 3, characterized in that: The organic solvent was butyl acetate.

6. The method for preparing a photovoltaic panel coating with anti-reflection and temperature control according to claim 2, characterized in that: The thiolactone acrylamide is prepared by the following steps: S1. dispersing 14-16 parts of DL-homocysteine ​​thiolactone hydrochloride in an organic solvent; S2, add 18-18.5 parts of acryloyl chloride and 24.5-25.5 parts of triethylamine dropwise to the solution obtained in S1, stir, and control the temperature at 0-5°C until the reaction is complete; S3, washing with water to remove the byproduct salt generated by the reaction, and evaporating to remove the organic solvent; S4, using an organic solvent as an eluent, purifying the product of S3 using a silica chromatography column to obtain thiolactone acrylamide; The above component parts are all by weight.

7. The method for preparing a photovoltaic panel coating with anti-reflection and temperature control according to claim 6, characterized in that: The organic solvent in step S1 is dichloromethane.

8. The method for preparing a photovoltaic panel coating with anti-reflection and temperature control according to claim 6, characterized in that: The organic solvent in step S4 is a mixed solution of ethyl acetate and n-hexane in a volume ratio of 1:

1.

9. The method for preparing a photovoltaic panel coating with anti-reflection and temperature control according to claim 2, characterized in that: The double-shell hollow nanoparticles are prepared by the following steps: B1. Dispersing 200-205 parts of nano-polystyrene microspheres and 75-85 parts of nano-indium tin oxide particles in a volatile organic solvent, wherein the particle size of the nano-polystyrene microspheres is 40-60 nm, and the particle size of the nano-indium tin oxide is less than half of that of the nano-polystyrene microspheres; B2, dispersing 15.5-16.5 parts of hexadecyltrimethylammonium bromide in an organic solvent, adding appropriate amounts of water and ammonia water, and mixing to form a uniform solution; slowly adding 155-165 parts of tetraethyl silicate, mixing and reacting completely, and the amount of water added is sufficient to allow the tetraethyl silicate to react completely; B3. After evaporating and removing the organic solvent, the reaction product is placed in a muffle furnace and calcined to remove the polystyrene microsphere template, thereby obtaining double-shell hollow nanoparticles with an inner layer of indium tin oxide and an outer layer of silicon dioxide.

10. The method for preparing a photovoltaic panel coating with anti-reflection and temperature control according to claim 10, characterized in that: The organic solvent in steps B1 and B2 is both isopropanol.

Citation Information

Patent Citations

  • Insulating mold coating for high-transparent glass

    CN101289281A

  • Multi-shell coated composite hollow structure material, and preparation method and application thereof

    CN113921780A

Cited By

  • Nanometer polymer coating for improving generating capacity of photovoltaic panel through temperature control

    CN122234671A